Plutonium leachability from alternative transuranic incinerator ash waste forms - Neilson, R Jr; Colombo, P; Bradley, D (Brookhaven National Laboratory, 1980)
Leaching experiments were conducted to determine the rate of plutonium release from Portland cement, urea-formaldehyde, and polyester-styrene waste forms incorporating incinerator ash waste. A modified IAEA leach test procedure was employing using demineralized water, simulated WIPP Brine B, simplified sodium dominated groundwater, simplified calcium dominated groundwater and simplified bicarbonate dominated groundwater leachants. The data obtained provided a good fit to a diffusion release model for semi-infinite media. This model allows the calculation of effective diffusivities for plutonium release and provides a means for the prediction of long-term plutonium releases from full-scale waste forms. The effective diffusivities determined for Portland cement and polyester-styrene waste forms varied from 1.6 x 10/sup -22/ to 3.9 x 10/sup -20/ cm/sup 2//sec. Plutonium release was more rapid from urea-formaldehyde waste forms which exhibited effective diffusivities of 2.3 x 10/sup -18/ to 1.1 x 10/sup -14/ cm/sup 2//sec. The lowest release rates were obtained for leaching in WIPP Brine B. Effective diffusivities in the range of 10/sup -22/ to 10/sup -20/ cm/sup 2//sec result in predicted fraction plutonium releases of 1.9 x 10/sup -6/ to 1.9 x 10/sup -5/ in 10/sup 5/ years (neglecting decay) from 210 liter (55 gallon drum) waste forms. As a result of the low effective diffusivities determined and for the long half-lives of TRU radionuclides, waste form stability may be the primary determinant of activity release over the time period that must be considered for TRU waste disposal.